2018
DOI: 10.1111/ctr.13275
|View full text |Cite
|
Sign up to set email alerts
|

Eversion endarterectomy of the deceased donor renal artery to prevent kidney discard

Abstract: EE appears to be a safe and under-utilized procedure that may prevent discard of marginal donor kidneys and is associated with acceptable short-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The artery was carefully flushed in an antegrade manner to check for patency, integrity, leaks, or disruption. The procedure had acceptable short-term outcomes and can be promising [22].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The artery was carefully flushed in an antegrade manner to check for patency, integrity, leaks, or disruption. The procedure had acceptable short-term outcomes and can be promising [22].…”
Section: Discussionmentioning
confidence: 91%
“…In our study, 64.2% of the vascular abnormalities behind RNTK were atheromatous lesions. Khan et al in 2018 suggested that eversion endarterectomy (EE) appears to be a safe procedure that can prevent discard of marginal donor kidneys exhibiting severe atherosclerosis involving the renal artery. After a subintimal dissection of the Carrel aortic patch surrounding the renal artery, a complete eversion was performed with a subsequent removal cast.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of vascular hard stenotic plaques may imply a contraindication to deceased donor transplantation. Depending on the availability of the Carrel aortic patch, the location of hard stenotic plaque (involving ostium and extending into renal artery), length of plaque free renal artery (safe anastomosis generally requiring main renal artery 1.5 cm or longer), either resection of a segment of artery/ Carrel patch containing plaque (permitting end to side anastomosis in a similar fashion performed in living donor kidney transplantation) or eversion endarterectomy can be successfully performed as a rescue procedure but requires increased technical expertise [33].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the increasing number of ECD and of the aging of both donor and recipient population, atherosclerosis of the vascular axis of the graft and of the recipient is becoming a serious challenge in the field of organ transplantation (20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%